Clinical pharmacokinetics, pharmacodynamics, safety, and tolerability of JNJ-54175446, a brain permeable P2X7 antagonist, in a randomised single-ascending dose study in healthy participants. (December 2018) - Timmers, Maarten; Ravenstijn, Paulien; Xi, Liwen; Triana-Baltzer, Gallen; Furey, Maura; Van Hemelryck, Sandy; Biewenga, Jeike; Ceusters, Marc; Bhattacharya, Anindya; van den Boer, Maarten; van Nueten, Luc; de Boer, Peter
Background: Central nervous system-derived interleukin-1β plays a role in mood disorders. P2X7 receptor activation by adenosine-triphosphate leads to the release of interleukin-1β. Aims: This first-in-human study evaluated safety, tolerability, pharmacokinetics and pharmacodynamics of a novel central nervous system-penetrant P2X7 receptor antagonist, JNJ-54175446, in healthy participants. Methods: The study had three parts: an ascending-dose study in fasted participants (0.5–300 mg JNJ-54175446); an ascending-dose study in fed participants (50–600 mg); and a cerebrospinal fluid study (300 mg). Target plasma concentrations were based on estimated plasma effective concentration (EC)50 (105 ng/mL) and EC90 (900 ng/mL) values for central nervous system P2X7 receptor binding. Results: Seventy-seven participants received a single oral dose of JNJ-54175446 ( n =59) or placebo ( n =18). Area under the curve of concentration time extrapolated to infinity (AUC∞ ) increased dose-proportionally; maximum concentration (Cmax ) of plasma (Cmax, plasma ) increased less than dose-proportionally following single doses of JNJ-54175446. Because food increases bioavailability of JNJ-54175446, higher doses were given with food to evaluate safety at higher exposures. The highest Cmax, plasma reached (600 mg, fed) was 1475±163 ng/mL. JNJ-54175446 Cmax in cerebrospinal fluid, a proxy for brain penetration, was seven times lower than in total plasma; unbound Cmax, plasma and Cmax, CSF were comparable (88.3±35.7 vs 114±39 ng/mL). JNJ-54175446 inhibited lipopolysaccharide/3′-O-(4-benzoylbenzoyl)-ATP-induced interleukin-1β release from peripheral blood in a dose-dependent manner (inhibitory concentration (IC)50 :82 ng/mL; 95% confidence interval: 48–94). Thirty-three of 59 (55.9%) participants reported at least one treatment-emergent adverse event; the most common adverse event being headache (11/59, 18.6%). Conclusion: Plasma exposure of JNJ-54175446 was dose-dependent. No serious adverse events occurred. Single-dose administration of JNJ-54175446>10 mg attenuated ex-vivo lipopolysaccharide-induced interleukin-1β release in peripheral blood. Passive brain penetration of JNJ-54175446 was confirmed.